2017
DOI: 10.1039/c7tc00079k
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond-laser direct writing for spatially localized synthesis of PPV

Abstract: Conversion of PTHT into PPV is achieved by direct laser writing. Fs-laser pulses induce photo-thermal reactions due to two-photon absorption, resulting in the microscopic control of PPV polymerization. Such methodology is a promising way towards the fabrication of arbitrary polymeric microcircuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…3c, the salient Raman signals recorded at 1175 cm −1 , 1597 cm −1 and 1629 cm −1 matched literature reports for PPV. 30,42 A powder X-ray diffraction analysis revealed that the oxidized product was highly crystalline, 43 as indicated by the strong signal observed at 18.5°, and the broad signal recorded between 20°and 35°was agreement with literature data for PPV ( Fig. 3d).…”
Section: View Article Onlinesupporting
confidence: 88%
See 1 more Smart Citation
“…3c, the salient Raman signals recorded at 1175 cm −1 , 1597 cm −1 and 1629 cm −1 matched literature reports for PPV. 30,42 A powder X-ray diffraction analysis revealed that the oxidized product was highly crystalline, 43 as indicated by the strong signal observed at 18.5°, and the broad signal recorded between 20°and 35°was agreement with literature data for PPV ( Fig. 3d).…”
Section: View Article Onlinesupporting
confidence: 88%
“…For example, Mendonça described the synthesis of spatially resolved PPV by applying laser pulses to films of poly(xylyliden tetrahydrothiophenium chloride). 30 Photon absorption was shown to result in a photothermal reaction that facilitated the elimination of reactive byproducts, including sulfonium leaving groups and hydrochloric acid, and afforded PPV with a higher conjugation length than analogues prepared using conventional thermalbased approaches.…”
mentioning
confidence: 99%
“…So far, much effort has been devoted to produce diverse Au NPs, such as chemical reduction, electrochemical deposition, and film thermal treatment [9][10][11]. Besides, because of the unique interaction mechanism between femtosecond laser and materials (different from traditional laser or sun light), femtosecond laser created a lot of exciting new possibilities in micro/nano structure fabrication [12][13][14][15][16]. In general, two primary methods (top-down and bottom-up) are currently available for fabricating Au NPs by femtosecond laser.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low processability of PPV, owing its insolubility, hinders the fabrication of microcircuits with different geometries. Direct laser writing techniques, however, have enabled this issue to be overcome, since they allow 2D patterns to be designed, as demonstrated by the femtosecond laser micromachining of the PPV precursor . In that study, laser irradiation parameters were optimized to obtain the conversion of a precursor polymer, poly(xylene tetrahydrothiophenium chloride) (PTHT), into PPV, resulting in spatially localized regions of PPV surround by its precursor.…”
Section: Introductionmentioning
confidence: 99%